2020
DOI: 10.37135/ns.01.06.10
|View full text |Cite
|
Sign up to set email alerts
|

Mejoras al desempeño energético en edificaciones abordando los desafíos actuales del demand-side: Una revisión de contribuciones de Latinoamérica

Abstract: Debido a la actual crisis energética mundial y como resultado de los acuerdos de las naciones participantes, se han establecido medidas por las Naciones Unidas para superar los desafíos relacionados. A pesar de los esfuerzos para incluir a los países subdesarrollados en dicho proceso de decisión, la mayoría de las contribuciones continúan estando inclinadas al hemisferio norte. Así, este trabajo se enfoca en destacar los esfuerzos realizados por los países Latinoamericanos (LA), entre 2018-2020, para contribui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…This finding can open a wide range of new possibilities in the local market, increasing the potential for new energy policies, and providing the basis for undertaking a significant step towards transforming smart cities. In this regard, European energy and research programs have shown strong interest in collaborating with Latin American countries to help reach global energy goals [78].…”
Section: Discussionmentioning
confidence: 99%
“…This finding can open a wide range of new possibilities in the local market, increasing the potential for new energy policies, and providing the basis for undertaking a significant step towards transforming smart cities. In this regard, European energy and research programs have shown strong interest in collaborating with Latin American countries to help reach global energy goals [78].…”
Section: Discussionmentioning
confidence: 99%